(The Abundant Garden in Supplication with the Beautiful Names of God) by Sheikh Ma'ruf al-Nawdhi - المفتی, پ. د. ئومێد نەجمەدین جەمیل (Sulaimani Journal for Humanities, 2024)
Scholars in the Muslim community have always dedicated themselves to providing guidance and illuminating the path for all humanity, striving to achieve true servitude to God Almighty and to facilitate humankind's role in stewardship and stewardship of the earth. Supplication (du'a) holds a prominent place in the texts of Islamic law and the ancient and modern Islamic heritage. It has multiple avenues and approaches for research and study. Through this endeavor, we attempt to highlight one methodology that cultivates in individuals a commitment to supplication and its application, given its profound impact on the present and future of both the individual and society. Among the methods scholars have employed in supplication is the method of invoking God's Most Beautiful Names, in response to the Quranic command: "And to Allah belong the Most Beautiful Names, so invoke Him by them" (Al-A'raf 7:180). This method is more likely to be answered because the servant's weakness is more apparent, and God's majesty, perfection, and beauty are more evident. Scholars have explored various avenues in explaining and connecting with these Names, aiming to attain God's pleasure and love and to live in tranquility. These avenues include poetry and verse. It is no secret that the master of this field, Sheikh Ma'ruf al-Nawdahi al-Barzanji al-Kurdi (d. 1254 AH), possessed both scholarly and spiritual prowess in delving into this domain. He authored the poem "Al-Rawda al-Ghanna fi al-Du'a bi Asma' Allah al-Husna" (The Abundant Garden in Supplication with the Most Beautiful Names of God), compiling in its 210 verses 108 names or attributes of God Almighty. Through these, he offered supplications for the present and the future, making the path easily accessible for those seeking to connect a name or attribute with its meaning in their supplications. This unique work is the subject of this research, which aims to define the methodology of the Sheikh, the author and composer. We have employed inductive reasoning, descriptive analysis, and occasionally analytical methods in our explanation, hoping that this work will find its place among serious studies on the subject of this poem, as well as highlighting the significance of both the poem and its author. And God is the One who grants success.